Sinergi Tripusat Pendidikan dalam Menanamkan Perilaku Terpuji di Madrasah Ibtidaiyah Berbasis Pesantren - Muhammad Aminan Marzuki; Rizki Amalia Sholihah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aimed to determine the role of teachers and parents in shaping commendable behavior in pesantren-based Madrasah Ibtidaiyah (Islamic elementary schools). The research method in this study used a qualitative research type with a case study approach. The primary informants of this study were parents, teachers, and pesantren administrators. The results of this study found commendable forms of student behavior, namely politeness, respect for other people or friends, independence, obeying the law or discipline, and responsibility. The role of the teacher in shaping character was carried out by creating a climate in the school, making posts about good behavior that were placed on the wall, and creating a habituation program (morning parade, prayer, kiss the teacher’s hand, good behavior posters, and religious practices). Meanwhile, the excellent behavior emphasized by parents and pesantren administrators was independence, politeness in interactions, and religious guidance.